Hemodynamic variations and pitfalls during venoarterial extracorporeal membrane oxygenation and left ventricular apical unloading as bridge to heart transplantation. Issue 3 (September 2021) - Tsioulpas, Charilaos; Mandoli, Giulia Elena; Cameli, Matteo; Bernazzali, Sonia; Pastore, Maria Concetta; Simeone, Felicetta; Valente, Serafina; Maccherini, Massimo
Abstract: Despite the exponential increase in venoarterial extracorporeal membrane oxygenation (VA-ECMO) use during the past decade, adult cardiac ECMO is still accompanied by a high mortality rate. Moreover, although left ventricular distension is now a well-known drawback of VA-ECMO, there seems to be great variability in the hemodynamic management strategies and in the results reported among the various centers. Hemodynamic management of VA-ECMO can be even more challenging when complex configurations are deployed. Here we present and discuss an interesting case of a modified VA-ECMO that although it occurred a few years ago it is instructive for its hemodynamic implications and pitfalls. VA-ECMO can either save the patient or catalyze the deterioration of a compromised clinical condition and thus a close multiparametric monitoring is mandatory especially with complex ECMO arrangements. A thorough understanding of the hemodynamic changes and problems that may occur during these cases is necessary too. Ultimately, critical thinking along with a proactive approach for early referral to more specialized centers and immediate unloading of the left ventricle whenever it is deemed necessary, together may contribute to reduce the relatively high mortality rate with this type of support. <Learning objective: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) can either save the patient or catalyze the deterioration of a compromised clinical condition if support-related drawbacks are not correctly identified and promptly adjusted. Management of complex VA-ECMO configurations can be challenging and thus a thorough understanding and close multiparametric monitoring of the hemodynamic implications and pitfalls are necessary in order to prevent negative outcomes.>